2003
DOI: 10.1111/1467-8624.00622
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers' Use of Form Class Cues to Learn Descriptive Proper Names

Abstract: This study examined 3‐ and 4‐year‐old preschoolers' ability to learn proper names containing familiar descriptions. Children saw a novel creature with a familiar property (it was red) and heard either an adjective (“This is a red one”) or a descriptive proper name (“This is Mr. Red”). The creature was then transformed, losing the property (e.g., it became green). Children had to extend the word to either the transformed original creature or a new creature bearing the original property (another red creature). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…At 2 years of age, they are able to differentiate proper nouns from count nouns (Katz, Baker, & Macnamara, 1974), count nouns from mass nouns (Soja et al, 1991) and map novel labels embedded in an adjectival structure to object properties (Mintz & Gleitman, 2002). At 4 years of age, they can use form class cues (Hall, Waxman, Br edart, & Nicolay, 2003). In contrast, reliance on more complex Malay classifier such as those that depict objects with flexible characteristics (e.g., helai for two-dimensional, flexible objects such as a piece of cloth) only emerges when children are older, around 7 years of age, in agreement with the claim that Malay-speaking preschool children are inexperienced with classifiers until they enter formal education (Salehuddin & Winskel, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At 2 years of age, they are able to differentiate proper nouns from count nouns (Katz, Baker, & Macnamara, 1974), count nouns from mass nouns (Soja et al, 1991) and map novel labels embedded in an adjectival structure to object properties (Mintz & Gleitman, 2002). At 4 years of age, they can use form class cues (Hall, Waxman, Br edart, & Nicolay, 2003). In contrast, reliance on more complex Malay classifier such as those that depict objects with flexible characteristics (e.g., helai for two-dimensional, flexible objects such as a piece of cloth) only emerges when children are older, around 7 years of age, in agreement with the claim that Malay-speaking preschool children are inexperienced with classifiers until they enter formal education (Salehuddin & Winskel, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that young children can use syntactic information to interpret words as the proper names of individuals. By 24 months, children can use syntactic information (e.g., "This is a MEF" vs. "This is MEF") to distinguish proper nouns from count nouns (e.g., Hall et al, 2001;Katz et al, 1974), an ability that becomes rapidly more sophisticated (Hall et al, 2003;Sorrentino, 2001). However, to our knowledge, no previous research has investigated young children's learning of proper names for two new individuals simultaneously, nor have any studies investigated young children's ability to make use of newly learned proper nouns within the context of a transitive sentence.…”
mentioning
confidence: 99%